Spare parts inventory management using quantitative and qualitative classification - Oliveira, Fernanda (2018)
This paper focuses on the spare parts inventory management of a maintenance provider of the health sector, where the commitment to ensure to agreed customer service level and the guarantee of maximum availability of the devices are relevante issues.